1997
DOI: 10.1001/jama.1997.03550190072047
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Quality

Abstract: The goal of this article is to address, from the perspective of users of the health care system (consumers), the following questions: What are the most important health care quality gaps and/or challenges; what major changes should we anticipate in this area in the near future; and what should be the role of federal and state agencies, accreditation organizations, and philanthropic foundations in addressing these challenges? We discuss the needs, challenges, and potential action steps for increasing the promin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…4, 15 Traditionally, pediatric providers were considered specialists who are trained to treat medical problems specific to children; however, pediatric providers as a whole have embraced the role of primary care providers – tasked with prevention, health promotion, and providing coordination services to children and their families. 16 In fact, for a majority of children, pediatric providers take on the responsibility of delivering accessible, continuous, comprehensive, family centered, and coordinated care.…”
Section: Discussionmentioning
confidence: 99%
“…4, 15 Traditionally, pediatric providers were considered specialists who are trained to treat medical problems specific to children; however, pediatric providers as a whole have embraced the role of primary care providers – tasked with prevention, health promotion, and providing coordination services to children and their families. 16 In fact, for a majority of children, pediatric providers take on the responsibility of delivering accessible, continuous, comprehensive, family centered, and coordinated care.…”
Section: Discussionmentioning
confidence: 99%
“…Five demographic characteristics (age, sex, education, race/ethnicity, and reason for hospitalization) were anticipated to be relevant to perceptions of quality care (Chang et al, 2003; Cleary & Edgman-Levitan, 1997; Hancock et al, 2003); variations in these characteristics were sought during recruitment. After Institutional Review Board approval was obtained, potential participants who met the criteria were identified by care managers in adult hematology-oncology, cardiac, intensive care, and medical-surgical units in the hospital.…”
Section: Methodsmentioning
confidence: 99%
“…The complex nature of patient experience of care implies that the dimensions to be investigated should be identified from the patient’s perspective. Studies have highlighted that definition of quality, measurement of quality, and routine quality assessment and improvement were important steps toward incorporating the patient’s perspective [18]. In addition to patient satisfaction scores, understanding the needs, preferences, and expectations of patients regarding health-care services are therefore important in developing a measuring tool.…”
Section: Introductionmentioning
confidence: 99%